LES CRUES DE L’OUED ISSIL EN AMONT DE MARRAKECH (MAROC), UN RISQUE NATUREL RECURRENT THE FLOODS OF THE WADI ISSIL UPSTREAM OF MARRAKESH (MOROCCO), A RECURRING NATURAL HAZARD - Mehdi Saidi, Mohamed el; Bouloumou, Youssef; Ed-Daoudi, Souad; Aresmouk, Mohamed El Hassane (European Scientific Journal, ESJ, 2013)
The wadi Issil originates in the High Atlas of Marrakesh, at altitudes above 2000 m. The mountainous part of the watershed is characterized by significant slopes, a low-permeable bedrock and a widespread dense hydrographic network.Concerning precipitation, the upstream stations of the basin record heavy and high rainfall levels. The average value e.g. in Agaiouar is approximately 582 mm a year, which is close to what can be found in sub-humid lands.This hydrogeomorphic and rainfall situation is conducive to the development of sudden and very fast floods. The recently opened hydrometric station of Aït Bouzguia has recorded some floods over the last years with a fast rising time (from 1h15 to 1h30). Using the data recording at the station of Ouagjdite, located upstream of the basin, response times of 2h30 were collected. These short periods pose a major risk as they do not allow a prediction of such floods in due time.These types of flood are renown for their infrastructure damages in Marrakesh, especially in areas near the wadi Issil. They often lead to substantial costs and sometimes the loss of human lives. Wadi’s overflow phenomenon is also exacerbated by numerous rubble or household waste, being abandoned on the stream bed. These waste materials shrink the wadi’s section and reduce its conveyance accordingly. Furthermore, the reduced diameter of some waste water systems, notably bridges nozzles, increases the risk.Several land-use plannings have been submitted, some others have been applied and some are currently underway. They roughly consist in dredging and raising banks of some sections, and in building new bridges and protective reinforcement walls along the wadi’s shores. These actions should strengthen with the strict prohibition of waste and rubble disposal in the stream bed. This can be done by promoting awareness of people living close to the wadi and an overall improvement of the environment involved. Aside from that, there could be a broader and fruitful coordination between the Wilaya, the water administration, the municipalities and Civil Society.